Efektivitas Kegiatan Rohani Islam (Rohis) Dalam Meningkatkan Pendidikan Ibadah Siswa SMA di Yayasan Pendidikan Harapan Bangsa Kuala Kabupaten Langkat - Nur Sri Hasanah; Mardianto Mardianto (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Rohis extracurricular is one of the places that aims to develop religious character, extracurricular has the ideal potential to develop students' worship education. The reality of student worship education at Yayasan Pendidikan Harapan Bangsa Kuala High School, Langkat Regency has regressed. This study aims to determine the effectiveness of Rohis activities in improving student worship education. Analysis of the implementation, effectiveness, form, and supporting and inhibiting factors of Rohis activities. With descriptive qualitative research methods, surveys with data collection techniques in the form of interviews and literature study research. The findings of this study include: First, the implementation of activities is carried out once a week with the form of activities in it is the recitation and reading and writing of the Qur'an. Second, the effectiveness of this activity can be seen from students who are increasingly active in carrying out worship. Third, facilities and infrastructure, PAI teachers and Rohis Coaches become supporting factors for the running of Rohis activities. Researchers concluded that Rohis activities can have a very large effect on students so that they can improve worship education through various activities carried out. Keywords: Effectiveness, Extracurricular, Rohis, Worship Education.